The effect of sociomathematical norms and technology integrated instruction on 6th grade students understanding of altitude - Senger, Ezgi. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This action research study was designed to improve students’ conceptual under standing of the concept of the altitude. For this purpose, an instruction was designed in the environment enriched with sociomathematical norms which are sharing solutions, working collaboratively acceptable mathematical explanations and being free to make mistakes. To improve the learning environment, instruction enhanced with technology by using various simulations and GeoGebra as dynamic tool. Before and after the 5-week long instruction with forty-eight 6th grade students, The Altitude Test was im plemented to assess students’ conceptual understanding of the concept of the altitude and misconceptions related to the concept of the altitude. Teacher’s ﬁeld notes and classroom audio and board recordings were used to detect sociomathematical norms and use of technology in the classroom. Students’ views about sociomathematical norms and technology were determined by students’ journals. The results of Altitude test showed that students improved their understanding of the concept of the alti tude. The result of the pre and post-tests showed that students had misconceptions related to the concept of altitude. Sociomathematically enriched, technology incor porated instruction led to decreasing or eliminating many misconceptions related to the concept of altitude and improved students’ conceptual understanding. Students’ journals showed that students’ views about norms and technology in the classroom reﬂected their learning positively. The result of altitude tests and the frequency of the misconceptions were also parallel with students’ views. It can be stated from the ﬁndings that the instruction enriched with sociomathematical norms helped students improve their conceptual understanding.
Keywords: Mathematics -- Study and teaching (Secondary) -- Social aspects.; Social norms -- Case studies.